High‐Voltage Energy Harvesting and Storage System for Internet of Things Indoor Application. Issue 9 (9th September 2022) - Speranza, Roberto; Zaccagnini, Pietro; Sacco, Adriano; Lamberti, Andrea
Abstract : Energy Harvesting and Storage System In article number 2200245, Roberto Speranza, Andrea Lamberti and co‐workers show, that a dye‐sensitized solar module and an electrical double layer capacitor are integrated in the same device able to harvest and directly store energy from indoor illumination. The device achieves high output voltage even in low‐light conditions and can work as a self‐rechargeable energy source for Internet of Things sensor networks.